2021
DOI: 10.26748/ksoe.2021.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Fluid Resonance on the Performance of a Floating OWC Device

Abstract: In the present study, the performance of a floating oscillating water column (OWC) device has been studied in regular waves. The OWC model has the shape of a hollow cylinder. The linear potential theory is assumed, and a matched eigenfunction expansion method(MEEM) is applied for solving the diffraction and radiation problems. The radiation problem involves the radiation of waves by the heaving motion of a floating OWC device and the oscillating pressure in the air chamber. The characteristics of the exciting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Performing frequency-domain motion analysis of the FPSO, it was confirmed that roll motion had a much more negative effect on total radiation than pitch motion. Studies regarding mooring design have been released, even though they were for the different types of floating renewable platforms such as floating wave converters and wind turbines [16,17].…”
Section: Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Performing frequency-domain motion analysis of the FPSO, it was confirmed that roll motion had a much more negative effect on total radiation than pitch motion. Studies regarding mooring design have been released, even though they were for the different types of floating renewable platforms such as floating wave converters and wind turbines [16,17].…”
Section: Of 15mentioning
confidence: 99%
“…on total radiation than pitch motion. Studies regarding mooring design have been released, even though they were for the different types of floating renewable platforms such as floating wave converters and wind turbines [16,17].…”
Section: Geometric Details Of the Pilot Pv Platformmentioning
confidence: 99%
“…Linear (Airy) wave theory was used to describe the water particle kinematics. The incident wave power per unit crest width of a regular wave can be expressed as follows [40]: kg/m was applied for all simulation cases. Among the four locations, Buan exhibited the largest incident wave power.…”
Section: Single Hemispherical Floatmentioning
confidence: 99%
“…Linear (Airy) wave theory was used to describe the water particle kinematics. The incident wave power per unit crest width of a regular wave can be expressed as follows [40]:…”
Section: Single Hemispherical Floatmentioning
confidence: 99%
“…Many studies have focused on the power efficiency of WECs [3][4][5]. One way to increase the power efficiency is that WECs could be integrated with other marine structures, such as breakwaters or seawalls [6].…”
Section: Introductionmentioning
confidence: 99%